DIAGNOSTICS AND FEATURES OF THE FLOW OF HYPERMOBILITY SYNDROME IN CHILDREN - Dzhuraev Akhrorbek Makhmudovich; Alimukhamedova Feruza Shavkatovna (Galaxy International Interdisciplinary Research Journal, 2024)
Scientific and practical interest in joint hypermobility dates back to the late nineteenth century, when hereditary syndromes were described in the clinical picture of which, joint hypermobility was one of the leading symptoms. In 1967, Kirk (J. H. Kirk), Ansell (B. M. Ansell) and Bywaters (E. G. Bywaters) proposed the term "hypermobile syndrome" to characterize the pathology in patients with hypermobile joints and persistent musculoskeletal complaints in the absence of any other rheumatic disease. Since then, systematic study of this pathology within the framework of rheumatologically and orthopedic syndromes has begun